Effect of Pentosan Polysulphate Administration in Man on the Formation of Covalent Complexes Between Heparin Cofactor II and Thrombin Generated in Plasma by Contact Activation - Dol, F; Sié, P; Dupouy, D; Boneu, B (Thrombosis and Haemostasis, 1986)
An assay for the quantification of pentosan polysulphate (PPS) in plasma is described. As PPS has been shown to potentiate thrombin inhibition by the second heparin cofactor (HC II), the principle of this assay was to measure the formation of covalent complexes between HC II and the thrombin generated in plasma after contact activation and recalcification. The complexes were quantified by using purified 125I-HC II added to the plasma as a tracer and SDS-polyacrylamide gel electrophoresis (SDS-PAGE). The assay was sensitive to low PPS concentrations (limit of detection: 0.1 μg/ml) and therefore suitable for the measurement of PPS in plasma after its administration to man.The clearance of PPS was studied in 3 subjects receiving respectively 10, 50 and 100 mg intravenously (IV) and in 3 subjects receiving 35 mg subcutaneously (SC). PPS was still detectable 8 h after 50 and 100 mg IV and 6 h after 35 mg SC. The activated partial thromboplastin time (APTT) was, in comparison, relatively insensitive but for concentrations above 1 μg/ ml the values derived from the APTT and from the SDS-PAGE method fitted. The results were also in general agreement with those reported by McGregor et al. (5) who used a sensitive competitive binding assay. This indicates that low concentrations of PPS previously measured chemically are also pharmacologically active in plasma.
Keywords: Pentosan polysulphate; Heparin cofactor II; Anticoagulant